The Effect of Tax Sanctions and Tamansiswa's Leadership Trilogy on the Obedient Intentions of Prospective Taxpayers - Wardani, Dewi Kusuma; Veradika, Heni (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
a tax is an obligatory payment to the government that individuals or entities are legally required to make. This payment is non-negotiable, does not result in direct compensation, and is utilized by the state for the overall welfare of the people. Therefore, those who have met these requirements are obligated to pay the government by adhering to tax regulations. Taxpayer compliance can be defined as a behavior in which the taxpayer fulfills all obligations. This study aims to determine the effect of tax sanctions and the trilogy of tamansiswa leadership on the obedient intentions of prospective taxpayers. The object of this study is an Accounting student of Universitas Sarjana Wiyata Tamansiswa Yogyakarta. This study used a sample of 100 respondents who were active accounting students of Universitas Sarjanawiyata Tamansiswa Yogyakarta. Sampling method with convenience sampling method. Data analysis techniques are carried out by descriptive statistical analysis, classical assumption tests, multiple linear regression tests and SPSS-IBM Statistics 25 software. The results showed that tax sanctions had no effect on the compliant intentions of prospective taxpayers and the trilogy of tamansiswa leadership had a positive effect on the obedient intentions of prospective taxpayers.